Young widower : a memoir - Evans, John W. (John William), 1977- (River teeth literary nonfiction prize (Series), 2014)
John W. Evans was twenty-nine years old and his wife, Katie, was thirty. They had met in the Peace Corps in Bangladesh, taught in Chicago, studied in Miami, and were working for a year in Romania when they set off with friends to hike into the Carpathian Mountains. In an instant their life together was shattered. Katie became separated from the group. When Evans finally found her, he could only watch helplessly as she was mauled to death by a brown bear. In such a love story, such a life story, how could a person ever move forward? That is the question Evans, traumatized and restless.